Revitalising the inner city in the Asia Pacific Region through urban design: different approaches and scales of intervention - Kozlowski, Marek; Mohd Yusof, Yusnani (Faculty of Design & Architecture, Universiti Putra Malaysia, 2016)
In recent years the Asia-Pacific Region has witnessed a spate of revitalisation projects as part of a general trend in addressing blight and decay of inner city urban areas. Urban design has been globally recognised as one of the key instruments of physical transformation employed to enhance urban quality and achieve sustainable urban environments. In this article we explore the role of urban design in the revitalisation process. In order to capture a wider urban context, revitalization at a city wide level in Singapore, district level in Brisbane, Queensland Australia and neighbourhood level on the Gold Coast, Queensland, Australia is examined . The three case studies differ from each other in terms of city size, global context, local economy, urban policy and in the case of Singapore social profile and culture. The study revealed that urban design, not only has role in the revitalization process, but underpins the economic and social regeneration of blighted urban areas in all three cities.